IMPLEMENTASI STRATEGI PEMBELAJARAN INKUIRI BERBASIS KOLABORASI UNTUK MENINGKATKAN MOTIVASI DAN DAYA PIKIR PESERTA DIDIK DI SEKOLAH - Ketut Citra Kurniawan (UHN IGB Sugriwa Denpasar, 2025)
The dynamics of education in the modern era present complex challenges, especially in fostering students' learning motivation and critical thinking skills. Teachers are required to design active, meaningful, and student-centered learning strategies. This study aims to analyze the implementation of inquiry learning strategies combined with collaborative methods to improve students' motivation and thinking power. With a qualitative approach through literature studies, researchers reviewed various relevant journals, books, and documents to examine the impact of this strategy on student engagement and learning outcomes. The discussion includes an overview of SPI, the advantages and disadvantages of SPI, forms of SPI implementation such as discussions, assignments, experiments, and questions and answers, as well as strategic innovations through collaboration with other approaches such as CTL and Cooperative Learning and Gamification to increase flexibility and effectiveness. The results show that collaboration-based inquiry learning can significantly improve students' motivation, critical thinking, and independence. This strategy is in line with the objectives of the current curriculum which encourages students to become active knowledge seekers.